Shifts in trends of erectile dysfunction-related Google searches pre and post Covid-19 pandemic in Saudi Arabia - Raed M. Almannie; Meshari A. Alzahrani; Yazeed A. Alghtani; Moataz I. Altokhais; Hamad Alkhudhayri (Journal of Men's Health, 2025)
Background: Erectile dysfunction (ED) is defined as the inability to achieve or maintain penile erections that are sufficient for satisfactory sexual performance. It is a prevalent global health issue influenced by multiple physiological and psychological factors. The Covid-19 pandemic has significantly affected public health behaviors, including online health information-seeking patterns. This study aimed to evaluate ED-related online search trends in Saudi Arabia before, during and after the Covid-19 pandemic. Methods: Google trends (GT) was used to analyze search interest for “erectile dysfunction”, “sildenafil” and “tadalafil” across three periods: pre-pandemic (January 2016–February 2020), pandemic (March 2020–June 2022) and post-pandemic (July 2022–January 2024). The terms were chosen as they represent general ED awareness and the two most used phosphodiesterase type 5 (PDE5) inhibitors (“sildenafil” and “tadalafil”). Statistical analyses included the Mann-Kendall test for trend significance and one-way Analysis of Variance (ANOVA) with Bonferroni correction to compare search densities across study periods. Results: The average monthly percentage change (AMPC) for all search terms was 0.003 (p < 0.001). One-way ANOVA results revealed significant differences in search densities across the study periods (p < 0.001), showing a sustained post-pandemic increase compared with pre-pandemic levels. Sildenafil was the most searched ED medication in Saudi Arabia. Conclusions: This study highlights the pandemic-driven shift in ED-related online searches, which raises concerns for self-medication and emphasizes the importance of structured public health efforts to address ED awareness and treatment in Saudi Arabia.